Eksplorasi Kemampuan Pemecahan Masalah Matematika Ditinjau dari Tipe Kepribadian Idealis dan Rasional Mahasiswa Universitas Darussalam Ambon - Kasriana Kasriana; Rasid Ode (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2019)
This study aims to described students in solving problems based on personality type use instruments, personality type , problem solving and interview.The results of the study show:(1) understand the problems the subject of idealist only record that asked; (2) was making plans the subject could detect formula; (3) carry out a plan the subject of using formulas were formerly, although one measure. (1) understand the problems the subject type rational not have inscribed requirements enough and the requirements necessary; (2) was making plans subject to determine the steps the; (3) implement plan, problem solving skilled in algorithms and accuracy of. Basically type idealisdan rational capable of being searched the solution of given problem but not wrote with complete steps resolution.